2013
DOI: 10.3109/10641963.2013.789046
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the liver fatty acids byHibiscus sabdariffaLinnaeus (Malvaceae) infusion, its possible effect on vascular reactivity in a metabolic syndrome model

Abstract: We investigated the effects of Hibiscus sabdariffa Linnaeus (HSL)-fed infusion on the fatty acid (FA) profile in liver of metabolic syndrome (MS) rats and its possible effect on vascular reactivity. Body mass, intra-abdominal fat, triglycerides, insulin, blood pressure, saturated, monounsaturated FA, NEFAs, Δ(9)-, Δ(6)-desaturases and vasoconstriction were increased, while vasorelaxation, polyunsaturated FA, endothelial nitric oxide and [Formula: see text]/[Formula: see text] ratio decreased in MS versus Contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 46 publications
2
36
0
2
Order By: Relevance
“…The results show that triglycerides are increased in MS groups and decreased when compared to the C group and are similar to those obtained by Pettersson et al who induced MS in female rats by administering a high-fat diet (60%) over a period of 14 weeks and found a significant increase in triglycerides when compared to the C group [46]. Another study showed that hypertriglyceridemia, resulting from the intake of high carbohydrate diet in rats, was associated with hyperinsulinemia, increased SBP, and insulin resistance [47]. Moreover, decreased levels of ovarian hormones associated with menopause or ovariectomy have been related to a decrease in glucose uptake by insulin [48].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results show that triglycerides are increased in MS groups and decreased when compared to the C group and are similar to those obtained by Pettersson et al who induced MS in female rats by administering a high-fat diet (60%) over a period of 14 weeks and found a significant increase in triglycerides when compared to the C group [46]. Another study showed that hypertriglyceridemia, resulting from the intake of high carbohydrate diet in rats, was associated with hyperinsulinemia, increased SBP, and insulin resistance [47]. Moreover, decreased levels of ovarian hormones associated with menopause or ovariectomy have been related to a decrease in glucose uptake by insulin [48].…”
Section: Discussionsupporting
confidence: 79%
“…Cell membrane properties, particularly its fluidity, depend upon the fatty acid composition. In hyperinsulinemic states, increased saturated fatty acids lead to a decrease in the affinity and number of insulin receptors, which may cause insulin resistance associated with hyperinsulinemia [47]. Estrogens can improve insulin action by increasing receptor specific binding to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids (FA) and NEFAs were extracted and identified by gas liquid chromatography, from serum (100 μ L) and from the administrated RSV + QRC commercial mixture (50 μ g), using the method described previously [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several factors are involved in the development of MetS which are linked to adipose tissue dysfunction, one of them being the circulating free fatty acids (FFA). In a MetS model developed by our group, we have found alterations in serum lipid composition, that is, high levels of nonesterified fatty acids (NEFAs) and of monounsaturated fatty acids (MUFAs) which have been proposed as contributors of the acquisition of insulin resistance and hypertension [ 2 4 ]. Moreover, FFA and their derivatives trigger physiological responses such as adipogenesis and adipokine secretion [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Por tanto, flavonoides como las antocianinas ejercerían un efecto protector contra la peroxidación lipídica 61 . A favor de la hipótesis de que los flavonoides también incrementan la concentración de los AGPI mediante la modificación de la actividad enzimática o la expresión génica de las enzimas Δ5 y Δ6D, se ha informado que el consumo de una infusión de Hibiscus sabdariffa restaura la actividad de Δ5 y Δ6D en ratas inducidas a Síndrome Metabólico, relacionando este efecto al elevado nivel de antioxidantes en la infusión 62 . En caso de bovinos, el consumo de un extracto de cáscara de granada, rica en polifenoles, se tradujo en mayor contenido de EPA y DHA en leche, atribuyendo este efecto a una reducción en la bio-hidrogenación ruminal y al incremento de las rutas encargadas de la síntesis de AGPI-CL en la glándula mamaria 63 .…”
Section: Acción De Ppar-α En La Regulación De Las Desaturasasunclassified